Social Status in Student Networks and Implications for Perceived Social Climate in Schools - Sule Alan; Elif Bodur; Elif Kubilay; Ipek Mumcu (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We investigate how adolescents' social status in their peers' eyes shapes the way they view their social climate in secondary schools. Utilizing novel data on over 10,000 students, we construct comprehensive measures of social status and perceived social climate for each student, including a sense of belonging, perceived behavioral norms, and bullying experience. We show that while central and well-connected students are positive about their social environment, less central and socially isolated students view it as hostile. Our results highlight the importance of improving the relational dynamics of adolescents in disadvantaged schools to create better learning environments for all.
Keywords: A14; I20; I24; 330; social status; student networks; classroom climate